Understanding the epigenetic basis of sex differences in depression. Issue 1 (7th November 2016) - Hodes, Georgia E.; Walker, Deena M.; Labonté, Benoit; Nestler, Eric J.; Russo, Scott J.
Abstract : Epigenetics refers to potentially heritable processes that can mediate both lasting and transient changes in gene expression in the absence of genome sequence alterations. The field of epigenetics has introduced a novel understanding of the mechanisms through which the environment can shape an individual and potentially its offspring. This Mini‐Review examines the current literature exploring the role of epigenetics in the development of mood disorders such as depression. Depression is twofold more common in females, yet the majority of preclinical research has been conducted exclusively in male subjects. Here we discuss what is known about sex differences in epigenetic regulation and function and how this may contribute to the etiology and onset of mood disorders. © 2016 Wiley Periodicals, Inc.